Relative importance of family, site, and field placement timing on survival, growth, and yield of hatchery-produced Pacific oyster spat (Crassostrea gigas) - Degremont, Lionel; Bedier, Edouard; Soletchnik, Patrick; Ropert, Michel; Huvet, Arnaud; Moal, Jeanne; Samain, Jean-francois; Boudry, Pierre (Aquaculture, 2005)
Summer mortality has been reported in the Pacific oyster, Crassostrea gigas, for many years in different parts of the world. The causes of this phenomenon are complex. The multidisciplinary program "MOREST", coordinated by IFREMER, was initiated to understand the causes of summer mortality of Crassostrea gigas juveniles in France and to reduce its impact on oyster production. Within this program, three successive groups of bi-parental families were bred in a hatchery in 2001 and placed in the field during summer in three sites (Ronce, Riviere d'Auray, and Baie des Veys). This paper reports the relative importance of family, site and field placement timing for three characters of major importance for oyster production: survival, growth, and yield. At the end of the summer period, significant differences for the three characters were observed among sites and families for each group. Family effect was the largest variance component for survival, representing 46% of the total. Variance component analysis revealed that variation in yield among families depended either on survival or on growth according to the site. Significant family x environment interactions were observed for yield and survival but not for growth. No difference in survival was found among groups in the three sites at the end of the experiment, but a critical period of mortality was identified from late July until early September. The influence of environmental conditions, notably on reproductive allocation and its relationship with the studied traits, is discussed. (c) 2005 Elsevier B.V. All rights reserved.